2015
DOI: 10.1186/s11671-014-0705-2
|View full text |Cite|
|
Sign up to set email alerts
|

The enhanced anticoagulation for graphene induced by COOH+ ion implantation

Abstract: Graphene may have attractive properties for some biomedical applications, but its potential adverse biological effects, in particular, possible modulation when it comes in contact with blood, require further investigation. Little is known about the influence of exposure to COOH+-implanted graphene (COOH+/graphene) interacting with red blood cells and platelets. In this paper, COOH+/graphene was prepared by modified Hummers' method and implanted by COOH+ ions. The structure and surface chemical and physical pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Earlier publications have revealed that the FGNs will induce obvious toxicity when nanodispersed FGNs are exposed in living system, especially for applications in nanomedicine . However, recent studies have indicated that, when FGNs are applied for the surface coating of implants or membranes, no obvious blood and cell toxicity has been observed. It is believed that the reduced “face-to-edge” contact between the cell membrane and FGNs-based coatings may be the main reason for their enhanced cell adhesion and proliferation of modified implants. The nitinol alloy is often used as a biomedical implant due to its superior mechanical properties.…”
Section: Emerging Biological Applications Of Fgns-based Architecturesmentioning
confidence: 99%
“…Earlier publications have revealed that the FGNs will induce obvious toxicity when nanodispersed FGNs are exposed in living system, especially for applications in nanomedicine . However, recent studies have indicated that, when FGNs are applied for the surface coating of implants or membranes, no obvious blood and cell toxicity has been observed. It is believed that the reduced “face-to-edge” contact between the cell membrane and FGNs-based coatings may be the main reason for their enhanced cell adhesion and proliferation of modified implants. The nitinol alloy is often used as a biomedical implant due to its superior mechanical properties.…”
Section: Emerging Biological Applications Of Fgns-based Architecturesmentioning
confidence: 99%
“…[59,61] Large surface areas of nanomaterials [e.g., graphene oxide (GO), multiwalled carbon nanotubes] [30,62] with abundant -COOH groups may enhance the anticoagulant activity of composite nanocoatings. [63] A 16-phosphonylhexadecanoic acid/chitosan-functionalized GO (GOCS) composite coating prepared on AZ31B Mg alloy decreased platelet adhesion (to ≈59% of that of bare metal) and activation, as evidenced by a 48% increased expression of cyclic guanosine monophosphate (cGMP), which reflects platelet inhibition. In addition, the composite nanocoating exhibited more potent anti-platelet activity than the unmodified 16-phosphonyl-hexadecanoic acid coating; platelet adhesion was inhibited by 43% and the concentration of cGMP was increased by 22%.…”
Section: Preventing Vascular Stent Thrombosis and Restenosismentioning
confidence: 99%
“…The anticoagulation property of COOH + -functionalized graphene correlated with the surface wettability of the substrate. 75 Surface functionalization of graphene substrates provides additional chemical and physical properties for enhanced cell response. The addition of small chemical moieties on graphene or GO altered the cell−material interactions.…”
Section: Functionalized Graphene-derived Particlesmentioning
confidence: 99%